Nephropathy and growth hormone deficiency in a patient with mitochondrial tRNA(Leu(UUR)) mutation. - Yorifuji, T (1996)
A mitochondrial A 3243 G mutation in the tRNA(Leu(UUR)) gene was first described as a common cause of MELAS syndrome (mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like syndrome). This same mutation is also the cause of a totally different disorder, a subtype of diabetes mellitus which is inherited maternally and often associated with sensorineural hearing loss. In this paper, we report on a Japanese boy with A 3243 G who developed a previously undescribed combination of symptoms, nephropathy and growth hormone deficiency. The patient first presented with short stature and moderate mental retardation. Growth hormone (GH) provocation tests showed deficient growth hormone secretion. During the course of follow up, he presented with progressive nephropathy followed by the development of diabetes mellitus. The results of laboratory tests and renal biopsy were against incidental association of known types of nephropathy. On PCR-RFLP analysis, the percentage of mutated mtDNA was higher in the renal biopsy specimen than 12 peripheral blood leucocytes. Our case suggests that mitochondrial diseases should be taken into account when there is nephropathy of unknown cause. In addition, the presence of growth hormone deficiency may account for part of the mechanism leading to short stature commonly seen in these patients.